23 A review of the management of non-culprit pci following primary pci for stemi in a tertiary referral centre. (5th October 2017) - Wheen, P; Cadogan, D; McFadden, E
Abstract : Background: Robust evidence exists for Primary PCI of culprit lesions in the setting of a STEMI. Management of non-culprit lesions remains less clear, with evidence showing intervention of non-culprit lesions immediately following Primary PCI reduces unplanned revascularisation, but with no reduction in non fatal MI, or mortality, even when FFR guided revascularisation is used. Aims: To review current management of non-culprit lesions in a primary PCI tertiary referral centre in Ireland; to compare the rate of immediate non-culprit PCI with planned subsequent inpatient/outpatient PCI. Methods: We obtained retrospective data from our hospital's STEMI database of all patients who had a diagnosis of STEMI made between January 1st 2015 and December 31st 2015. We used the hospital's electronic record to obtain details of the initial diagnosis and Primary PCI procedure, as well as any subsequent interventions. We excluded patients who presented following cardiac arrest, or who were treated for cardiogenic shock with inotropes. We excluded patients who had previously undergone CABG. We excluded non-culprit lesions if they involved the left main stem, or if they were chronic total occlusions. Results: 178 patients (36 female (20.2%)) were diagnosed with a STEMI in the study period. 100% of these were taken for Primary PCI, of whom 95.0% underwent successful treatment of the culprit lesion. Of the 169 patients who had successful treatment of the culprit lesion, 116 (68.6%) had more than 1 vessel disease, with 88 (52.1%) having a non-culprit lesion >50%. 25 of these patients had presented following cardiac arrest (12), had cardiogenic shock (5), CTO (1), previous CABG (4), or non culprit LMS (3). Of the remaining 63 STEMI patients who had successful treatment of the culprit lesion, only 3 patients underwent non-culprit PCI during the initial procedure, a further 15 patients underwent staged PCI (10 during the initial admission). Overall, within the 178 patients presenting with STEMI, 19 patients underwent staged PCI following STEMI, with 12 of these occurring during the same inpatient stay. 7 patients were referred for CABG. Conclusions: 4.8% of patients who were potentially eligible for non-culprit PCI following successful primary PCI of culprit lesions underwent further PCI of non-culprit lesions during the initial procedure, with a further 25% of these patients undergoing PCI in a staged manner. This shows a low rate of non-culprit PCI during the initial procedure, despite 10.7% of all STEMI patients undergoing staged PCI after the initial primary PCI.